RANCANG BANGUN ALAT SETTING ALIGNMENT RODA GIGI SEBAGAI MEDIA PEMBELAJARAN DI LABORATORIUM PERBAIKAN DAN PEMELIHARAAN MESIN - Kadriadi Kadriadi; Angga Bahri Pratama; Kadex Widhy Wirakusuma; Jandri Fan HT Saragi; Jeri Ariksa; Muhammad Alfian; Yudi Siswanto (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
Alignment is a technique used to maintain machine components that rotate or transfer power so they can operate as effectively as possible and prevent damage to other machine components from errors made during installation or maintenance. Alignment is a maintenance activity that is often carried out on machines in industry and machines within the Morowali Metal Industry Polytechnic, especially in the Mechanical Maintenance Engineering Study Program. Competency in the alignment of gears and bearings is very much needed for prospective mechanics in the industry. The purpose of making this tool is as a simulation tool for learning alignment to achieve straightness and centricity between two rotating shafts (drive and driven shaft) to prevent friction, vibration, and other problems that can reduce tool life and, of course, increase expenditure costs. for repair or replacement of heavy equipment. In the process of designing this alignment tool, a drive method is used in the form of a sprocket and chain, where the link between the drive motor and the shaft to be moved is the sprocket and chain method. This research serves to help produce a design by considering the user's perspective so that the design results can be useful effectively. From the test results, the gear alignment setting tool can function well with the help of an inverter so that motor rotation can be reduced and can be controlled according to the desired conditions. The previous alignment setting tool had an RPM: of 1450.8 and the alignment setting tool that was made had an RPM: of 1455.7 with a frequency of 50 Hz so it can be concluded that this tool can be used for practical work in machine repair and maintenance laboratories.